2020
DOI: 10.17576/jsm-2020-4901-25
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Marangoni Flow Past a Permeable Stretching/Shrinking Sheet in a Hybrid Cu-Al2O3/Water Nanofluid

Abstract: The present study accentuates the Marangoni convection flow and heat transfer characteristics of a hybrid Cu-Al 2 O 3 / water nanofluid past a stretching/shrinking sheet. The presence of surface tension due to an imposed temperature gradient at the wall surface induces the thermal Marangoni convection. A suitable transformation is employed to convert the boundary layer flow and energy equations into a nonlinear set of ordinary (similarity) differential equations. The bvp4c solver in MATLAB software is utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Moreover, dual solutions of hybrid nanofluid flow were examined by Waini et al [34][35][36][37][38][39]. Other physical aspects have been considered by several authors [40][41][42][43][44][45][46][47][48][49] and review papers are also available [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dual solutions of hybrid nanofluid flow were examined by Waini et al [34][35][36][37][38][39]. Other physical aspects have been considered by several authors [40][41][42][43][44][45][46][47][48][49] and review papers are also available [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…However, the imposition of the adequate suction could generate the non-unique solution. In this regards, there have been some studies in the literature reporting the problem of the flow over the shrinking sheet in a hybrid nanofluid such as Aladdin et al (2020), Anuar et al (2020), Khan et al (2020b), Khashi’ie et al (2020c, 2020d, 2020e), Waini et al (2020c, 2020d, 2020e, 2020f, 2021), Yashkun et al (2020), and Zainal et al (2020a, 2020b, 2020c). For further reading, the readers are encouraged to refer to the review papers on the hybrid nanofluids available in the literature (Sarkar et al , 2015; Babu et al , 2017; Huminic and Huminic, 2020; Yang et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the heat transfer rate of the hybrid nanofluid is higher than that of the regular nanofluid. Moreover, the non-uniqueness of the solutions in the hybrid nanofluid flow was examined by Waini et al [21][22][23][24][25][26][27] Other physical aspects were considered by several authors [28][29][30][31][32][33][34][35]. Furthermore, the review papers can be found in [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%